2016
DOI: 10.1074/jbc.m115.704734
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Regulation of Bone Morphogenetic Protein Activity by the Microfibril Component Fibrillin-1

Abstract: Since the discovery of bone morphogenetic proteins (BMPs) as pluripotent cytokines extractable from bone matrix, it has been speculated how targeting of BMPs to the extracellular matrix (ECM) modulates their bioavailability. Understanding these processes is crucial for elucidating pathomechanisms of connective tissue disorders characterized by ECM deficiency and growth factor dysregulation. Here, we provide evidence for a new BMP targeting and sequestration mechanism that is controlled by the ECM molecule fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 46 publications
3
85
0
Order By: Relevance
“…Heparin also reduced BMP-2 interaction with its antagonist noggin by modulating its distribution on the cell surface with prolonged half-life[55]. Extracellular regulation of BMP activity by other ECM proteins was also studied that BMP-7 underwent conformational change from bioactive open V-shape to latent closed ring shape upon binding to fibrillin-1[56]. …”
Section: Discussionmentioning
confidence: 99%
“…Heparin also reduced BMP-2 interaction with its antagonist noggin by modulating its distribution on the cell surface with prolonged half-life[55]. Extracellular regulation of BMP activity by other ECM proteins was also studied that BMP-7 underwent conformational change from bioactive open V-shape to latent closed ring shape upon binding to fibrillin-1[56]. …”
Section: Discussionmentioning
confidence: 99%
“…Some fibrillin‐1 mutations may also disrupt BMP prodomain interactions with fibrillin‐1 (Wohl et al . ), altering BMP signals which regulate musculoskeletal growth.…”
Section: ‘Tall’ Fibrillinopathiesmentioning
confidence: 99%
“…However, latent TGF-b also binds other matrix components such as fibronectin (Horiguchi et al 2012), whilst LTBP-1 also independently multimerizes in a heparin-/HS-dependent manner . In contrast, fibrillin-1 can directly bind prodomains of BMPs 2, 4, 5, 7 and 10, inducing a conformational change that blocks BMP interactions with its receptors (Gregory et al 2005;Sengle et al 2011;Wohl et al 2016).…”
Section: Microfibril-associated Moleculesmentioning
confidence: 99%
“…The complex has been reported to resemble the overall shape displayed by proBMP9 (Wohl et al, 2016). Interestingly, the authors observed that proregion-mediated binding to fibrillin induced a conformational switch that could be observed by electron microscopy.…”
Section: The Functionally Versatile Bmp Proregionsmentioning
confidence: 81%